Effect of carbonate-containing self-healing system on properties of a cementitious composite: Fresh, mechanical, and durability properties. (28th February 2020) - Wang, X.F.; Yang, Z.H.; Fang, C.; Wang, Weilun; Liu, Jian; Xing, F.
Highlights: Self-healing system greatly affected fresh properties of cementitious composite. Inclusion of self-healing system improved the compressive and flexural strength. The carbonate-containing self-healing system showed great healing efficiency. The durability properties of self-healing concrete were studied. Abstract: Lightweight clay aggregate (LWA) impregnated with liquid sodium carbonate was used for autonomous self-healing of cementitious composites. This study investigated the effect of a carbonate-containing healing system on the fresh, mechanical, and durability properties of a cementitious composite and the fluidity, early-age hydration characteristics, flexural and compressive strength, the permeability of chloride ions, and the polarization resistance were evaluated. The self-healing potential was assessed by conducting tests on the crack area and healing products. The results showed that although the seepage of sodium carbonate significantly reduced the polarization resistance, the self-healing properties and the fresh and hardened properties of the concrete were improved. Scanning electron microscopy (SEM) observations showed that the healing products were present both in the interior and at the mouth of the crack surface. The X-ray diffraction (XRD) patterns indicated that the crystals obtained from the crack surface consisted mostly of calcite.